Farmer Behaviour of Certified High-Yielding Seed Users Increases Tobacco Productivity - Suganda, Dudung Ahmad; Dina, Dina; Apriliani, Diah (STKIP Singkawang, 2024)
Superior seeds are certified as one of the determinants of increasing productivity. Farmer behaviour is also one of the keys to increasing productivity. This research used a descriptive qualitative approach. The subject of this study was 11 farmer groups in 8 districts. Data was obtained through in-depth interviews and participatory observation of tobacco farmers in several major tobacco-producing regions and data analysis using triangulation. The seeds of the Kubangsari variety had high production and the largest percentage yield compared to other varieties. The behaviour model of farmers using certified superior seeds could increase tobacco productivity and the behaviour of farmers who used certified superior seeds of Kubangsari varieties had the highest productivity level of 22,826 kg/ha the highest than varieties of timing, hence, Tanjung, Citrasari, and sigh. Therefore, seeds could be selected or determined to be cultivated more massively in locations that had similar microclimate characteristics to increase profits. The contribution of this research can be used as one of the materials for planning and evaluating seed activities in the tobacco commodity development area.